HUBUNGAN PENGETAHUAN ANGGOTA IDI TENTANG KODE ETIK KEDOKTERAN TERHADAP SIKAP UPAYA MENINGKATKAN KERAHASIAAN REKAM MEDIS DI JAKARTA SELATAN TAHUN 2020 - Tobi Arna Dalimunthe (2020)
Medical record is a file contained record and documentation about identification of patient, treatment and other care provider of patient. Medical Ethics of Indonesia is principles for a doctor to guide the care provider and health's provider, include of guide ethic principle and rule about medical record. Medical Ethics of Indonesia made and arranged by doctor who join to Ikatan Dokter Indonesia (IDI) organization. This study aimed to search the relation of medical ethics of Indonesia's knowledge of member IDI South Jakarta to the attitude to increase of protect the secret of medical record period 2020. This study was an analytical observational study with a cross sectional design. The sample of this study was 96 members of IDI South Jakarta taken by simple randome sampling. The result of univariat analysis are the majority of sample is women, age 26-36 years old (adult), the most sample have low knowledge of Medical Ethics of Indonesia, sample have high attitude to increase of protect the secret of medical record. This study was analyzed by Chi-Square test. Chi-Sqaure test result showed that there wasn't relation between medical ethics of Indonesia's knowledge of member IDI South Jakarta with the attitude to increase of protect the secret of medical record (p = 0.165). This study concluded that medical ethics of Indonesia's knowledge of member IDI South Jakarta didn't relate to the attitude to increase of protect the secret of medical record period 2020, because There are many factor that affect to attitude attitude to increase of protect the secret of medical record i.e. personal experience, information from people or people who important.